ENHANCING RURAL COMMUNITY DEVELOPMENT THROUGH POLITICAL TRANSPARENCY - Padilah, Ahirul Habib; Alamri, Annisa Rizqa; Apriyani, Eka; Rudiyanto, Yustinus (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2023)
Political transparency plays a pivotal role in strengthening active participation and awareness of rural communities in local development processes. . This study aims to analyze the role of political transparency in shaping empowered and resilient rural communities. The primary focus is to understand the positive impact of political transparency on active participation of village residents, enhancing accountability of local government, and driving sustainable development. The research employs a qualitative descriptive analysis approach, combining primary and secondary data. Primary data is gathered through interviews with local leaders, community figures, and village residents, while secondary data is derived from official documents and relevant literature studies. The findings indicate that the implementation of political transparency significantly enhances the participation of rural communities in the development process.